2011
DOI: 10.1097/gme.0b013e31821fc8e0
|View full text |Cite
|
Sign up to set email alerts
|

The role of soy isoflavones in menopausal health

Abstract: Several areas for further research have been identified on soy and midlife women. More clinical studies are needed that compare outcomes among women whose intestinal bacteria have the ability to convert daidzein to equol (equol producers) with those that lack that ability (equol nonproducers) in order to determine if equol producers derive greater benefits from soy supplementation. Larger studies are needed in younger postmenopausal women, and more research is needed to understand the modes of use of soy isofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 215 publications
2
50
0
Order By: Relevance
“…Their actions in bone are believed to be mediated by binding to estrogen receptor (ER) α or β, which subsequently leads to the alteration of gene transcription via interaction with estrogen response elements (EREs) in the promoters of target genes [12]. However, concerns have been raised regarding the potential unintended side effects of soy isoflavones in other estrogen sensitive tissues [13]. On the other hand, the most commonly consumed flavonoids in both Western and Asian countries were flavan-3-ols, especially those found in tea.…”
Section: Introductionmentioning
confidence: 99%
“…Their actions in bone are believed to be mediated by binding to estrogen receptor (ER) α or β, which subsequently leads to the alteration of gene transcription via interaction with estrogen response elements (EREs) in the promoters of target genes [12]. However, concerns have been raised regarding the potential unintended side effects of soy isoflavones in other estrogen sensitive tissues [13]. On the other hand, the most commonly consumed flavonoids in both Western and Asian countries were flavan-3-ols, especially those found in tea.…”
Section: Introductionmentioning
confidence: 99%
“…Supplements commonly contain soy protein which is a rich source of isoflavones; specifically genistein, daidzein, and glycitein. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have suggested that supplementation with purified soy isoflavones may improve cognitive performance, in both men and women (Gleason et al, 2009; Thorp et al, 2009). However, these studies were based on relatively small subject numbers and it remains uncertain whether soy isoflavone supplementation has beneficial effects, in larger human populations (Clarkson et al, 2011). …”
Section: Discussionmentioning
confidence: 99%